Peranan Audit Operasional dalam Pemeriksaan Sumber dan Penggunaan Dana pada PT. BPR Eka Prasetya Medan - Liskauli Sinaga; Zainal Abidin; Rosmaini Rosmaini (Economics, Business and Management Science Journal, 2023)
xThe purpose of this study was to determine the role of operational audit in examining sources and uses of funds at BPR Eka Prasetya Medan. The formulation of the problem in this study is "What is the role of the operational audit in examining the sources and use of funds at BPR Eka Prasetya"?. Auditing is "An examination that is carried out critically and systematically by an independent party, on the financial statements that have been prepared by management along with the accounting records and supporting evidence, with the aim of being able to provide an opinion regarding the fairness of the financial statements". BPR Eka Prasetya Medan, prepares a cash flow statement using the indirect method, in which this method reports cash flows prepared based on cash/bank. The method of preparing the statement of cash flows is indirectly prepared based on the income statement and balance sheet. changes in cash inflows (inflows) and cash outflows (outflows) as presented in cash flows in operating activities are as follows, in 2011 the value of Rp. 894,055,200, - while in 2012 it was Rp. 610,441,800,-. Changes in operating cash flow can be seen from 2011 to 2012 of (Rp. 283,610,400) the company's operating cash flow experienced a decrease or was negative. After doing a comparison between theory and practice regarding the role of operational audit in the source and use of funds on cash flow as a tool in increasing the effectiveness and efficiency of the company. This can also be seen from the procedures carried out by BPR Eka Prasetya in avoiding misappropriation of incoming and outgoing cash.